Backfield Blow - Jake Maddox (Stone Arch Books, 2022)
Nothing can stop star running back Harris Weathers--until he takes a jarring hit, narrowly escaping injury. Harris is fine, physically, but his nerves are rattled. He can't shake the idea that he could get hurt playing football. After faking illness to get out of a game, Harris realizes he has a decision to make. Does he love football enough to risk a big hit again? And is there anything he can do to keep himself safe while playing the game he loves?
Keywords: Sport Stories -- Sport Stories